Influence of interoception and body movement on the rubber hand illusion - Kaneno, Yoshitaka; Pasqualotto, Achille; Ashida, Hiroshi (Frontiers in Psychology, 2024)
Rubber hand illusion (RHI) refers to the illusory sense of body ownership of a fake hand, induced by synchronous visuo-tactile stimulation to the real and fake hands. Negative correlation was reported between the cardiac interoception and the strength of RHI, but following studies have failed to replicate it. On the other hand, voluntary action is suggested to link interoception and the sense of body ownership in different situations. If so, moving RHI, induced by active or passive finger tapping while observing a fake hand, might reveal the relationship more clearly. Measurement of interoception has been another issue. We therefore examined the relationship between the moving RHI and two measures of interoception; interoceptive accuracy (IAcc) measured by the conventional heartbeat counting task, and interoceptive sensibility (IS) measured by a questionnaire. For the classical visuo-tactile RHI, our results supported the lack of association between the interoception measures and RHI. For the moving RHI, stronger sense of body ownership was induced for participants with higher IS regardless of active or passive movement, and stronger sense of agency was induced by active than passive movement only for those with lower IAcc. These results reveal the dynamic links between interoception and the bodily senses. The results also suggest that multiple dimensions of interoception affect the bodily senses differently.